2015
DOI: 10.1155/2015/531242
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Serous Psammocarcinoma of Ovary: Rare Variant Low Grade Serous Carcinoma

Abstract: Serous psammocarcinoma is a rare variant of serous carcinoma arising from either ovary or peritoneum, characterized by massive psammoma body formation, low grade cytologic features, and invasiveness. Its clinical behavior is similar to serous borderline tumors with relatively favorable prognosis. We report herein a case of a 60-year-old postmenopausal woman who presented with abdominal distension. Contrast enhanced computed tomography (CECT) revealed calcified pelvic masses with ascites. Elevated serum CA-125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…9 Clinically, patients usually present with nonspecific symptoms, such as abdominal discomfort, increase in abdominal girth, nausea, or vomiting. 10 In 40% of cases, PPP is asymptomatic and is discovered incidentally, 11 similar to our case and the case described by Grinaldi et al 3 The diagnosis of PPP is based on histopathological findings. Microscopically, Gilks et al define psammocarcinoma by four specific histologic criteria: (i) a destructive invasion of ovarian stroma, a vascular invasion, or, in the extraovarian cases, an invasion of intraperitoneal viscera; (ii) a mild to moderate nuclear atypia; (iii) an absence of area of solid epithelial proliferation, except for occasional nests with no more than 15 cells in diameter; (iv) at least 75% of papillae associated with or totally replaced by psammoma bodies.…”
Section: Discussionsupporting
confidence: 86%
“…9 Clinically, patients usually present with nonspecific symptoms, such as abdominal discomfort, increase in abdominal girth, nausea, or vomiting. 10 In 40% of cases, PPP is asymptomatic and is discovered incidentally, 11 similar to our case and the case described by Grinaldi et al 3 The diagnosis of PPP is based on histopathological findings. Microscopically, Gilks et al define psammocarcinoma by four specific histologic criteria: (i) a destructive invasion of ovarian stroma, a vascular invasion, or, in the extraovarian cases, an invasion of intraperitoneal viscera; (ii) a mild to moderate nuclear atypia; (iii) an absence of area of solid epithelial proliferation, except for occasional nests with no more than 15 cells in diameter; (iv) at least 75% of papillae associated with or totally replaced by psammoma bodies.…”
Section: Discussionsupporting
confidence: 86%
“…In the review of 5 patients with primary psammocarcinoma of the ovary or peritoneum by Poujade et al, benefits of adjuvant chemotherapy were poorly defined in these low-grade tumors with a low mitotic index ( Poujade et al, 2009 ). However, for treatment, most authors do agree and recommend aggressive cytoreduction initially, as is seen with this patient ( Jena et al, 2015 ). The effectiveness of letrozole as hormonal maintenance therapy for ovarian cancer was evaluated by Gershenson et al This showed that after primary treatment of cytoreductive surgery and platinum-based chemotherapy, the use of letrozole (n = 38) had significantly longer median progression-free survival than patient who underwent routine observation (n = 133) (64.9 months vs 26.4 months, p < 0.001).…”
Section: Discussionmentioning
confidence: 84%
“…Though the presence of psammoma bodies is noted and have generally shown to have good prognostic value, the rarity of this incidental finding obscures this value. Based on literature review, these tumors have a better prognosis than invasive serous adenocarcinoma ( Jena et al, 2015 ). Though most seem to follow an indolent course similar to borderline tumors of the ovary, aggressive clinical behavior with distant metastasis and recurrence is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing previous reports, we found that 23 out of 26 patients bearing psammocarcinom of ovary were advanced at FIGO stage III-IV (88%), which indicates a trend similar to that of ovarian high-grade serous carcinoma. 1,[10][11][12][13][14][15][16][17][18][19][20][21][22] The survival rate is higher than that of high-grade serous carcinoma and is comparable to that of borderline malignant serous tumors, and the 5-year survival rate of patients at stage I has been reported to exceed 95%. 23,24 Even in advanced cases, the rate of recurrence is low, and in cases of recurrence, the progression is gradual and follows a long-term course.…”
Section: Discussionmentioning
confidence: 99%